Principles of electrocatalysis by hydrogen activating metalloenzymes - Hexter, SV (2014)
Hydrogenases catalyse the interconversion of H2 and H+. Protein Film Electrochemistry (PFE), a technique in which a redox enzyme is adsorbed directly onto an electrode, enables a detailed description of the catalytic function of these metalloenzymes to be obtained. Unlike small-molecule electrocatalysts, the hydrogenase active site is surrounded by a protein structure ensuring that it is relatively unperturbed by the electrode surface. In this thesis, PFE is used alongside mathematical modelling to explain diﬀerences between [NiFe]- and [FeFe]-hydrogenases, highlighting some important considerations for eﬃcient, reversible electrocatalysis. This thesis probes the unusual reaction between [NiFe]-hydrogenases and cyanide. Through a detailed study utilising PFE, Electron Paramagnetic Resonance (EPR) and Attenuated Total Reﬂection Infrared spectroelectrochemistry (ATR-IR), it is demonstrated that cyanide promotes the formation of the inactive Ni-B state. Preferred formation of the Ni-B state over more slowly reactivating Unready states is considered an important characteristic of the O2-tolerant class of [NiFe]-hydrogenases. The nature of the Ni-L state, commonly thought to be an artefact formed when a [NiFe]-hydrogenase is exposed to visible light, is probed via EPR and ATR-IR. In this thesis, the Ni-L state is shown to occur in samples of Hydrogenase-1 from Escherichia coli that have not been exposed to visible light, calling into question the true nature of this state. Finally, this thesis details the ﬁrst study in which PFE is used to investigate the spontaneous incorporation of a synthetic active site mimic complex into apo-hydrogenase. Incorporation into apo-hydrogenase from Chlamydomonas reinhardtii and Clostridium pasteurianum is discussed, in both cases resulting in fully functional [FeFe]-hydrogenase, electrochemically indistinguishable from the native enzyme.